(untitled) (Journal of Pharma Insights and Research, 2025)
A rapid, sensitive, and specific reverse-phase high-performance liquid chromatography (RP-HPLC) method was developed and validated for simultaneous estimation of Empagliflozin and Sitagliptin Phosphate in pharmaceutical formulations. The chromatographic separation was achieved using a C18 column (250 mm × 4.6 mm, 5 μm) with mobile phase consisting of methanol and 0.05% acetic acid (45:55 v/v) at a flow rate of 0.9 mL/min. Detection was carried out at 254 nm with retention times of 2.75 and 3.77 minutes for Sitagliptin Phosphate and Empagliflozin respectively. The method demonstrated linearity over concentration ranges of 50-150 μg/mL for both drugs with correlation coefficients >0.999. The developed method was validated according to ICH guidelines for accuracy, precision, specificity, linearity, robustness, and stability. Recovery studies showed mean recoveries of 99.99-100.51% for both analytes. The method showed good precision with RSD values <2% for both intra-day and inter-day studies. Forced degradation studies confirmed the stability-indicating nature of the method. The validated method proved to be simple, rapid, precise and accurate for routine quality control analysis of Empagliflozin and Sitagliptin Phosphate in pharmaceutical formulations